2015
DOI: 10.1002/cpp.1962
|View full text |Cite
|
Sign up to set email alerts
|

Is Seeing Believing? The Process of Change During Cognitive–behavioural Therapy for Distressing Visual Hallucinations

Abstract: Distressing visual hallucinations (VH) are a relatively common symptom of psychosis. Visual hallucinations seem to be associated with greater impairment and disability. We have no specific treatment for VH. The appraisal of the visual experience and the behavioural response is important in maintaining the distress. Cognitive-behavioural therapy for VH at present has limited value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 30 publications
0
24
0
2
Order By: Relevance
“…Although visual hallucinations occurred at a lower prevalence than auditory hallucinations, and for many patients were a memory rather than a current phenomenon, they are often distressing (Dudley et al, 2012) and, at present, there is no evidence base supporting specific interventions for visual hallucinations in psychosis (Wilson et al, 2015). Further research examining the efficacy of novel treatments for visual hallucinations is required (Wilson et al, 2015).…”
Section: Hallucinations In Schizophrenia 15mentioning
confidence: 99%
“…Although visual hallucinations occurred at a lower prevalence than auditory hallucinations, and for many patients were a memory rather than a current phenomenon, they are often distressing (Dudley et al, 2012) and, at present, there is no evidence base supporting specific interventions for visual hallucinations in psychosis (Wilson et al, 2015). Further research examining the efficacy of novel treatments for visual hallucinations is required (Wilson et al, 2015).…”
Section: Hallucinations In Schizophrenia 15mentioning
confidence: 99%
“…Possible clinical implications of this work are that a brief normalising rationale that explains that visions are common, and are a result of impaired perceptual processes may be helpful and reduce distress in people with ED, or PD. Where there is cognitive impairment or particularly in people with psychosis, where multimodality is common and conviction and distress are high, it may be that normalisation alone may be insufficient and a number of reality testing approaches are needed to help the person learn that their vision cannot cause them harm, and that they are safe (Wilson et al, 2016). <0.001 Z,B,C,D,E,F , 0.601 A , 0.013 C n = 2 ¥ n = 39 ¥ n = 18 ¥ n = 22 ¥ Olfactory (%) 0 (0) 1 (2.6) 1 (5.6) 6 (27.3) Data are n (%); Statistics are chi-square (χ 2 ) or Fisher's exact tests; ED = Eye disease; PD = Parkinson's disease; LBD = Lewy body dementia; MMH = multimodal hallucinations Z comparison across all groups: df = 3; A ED vs. PD: df = 1; B ED vs. LBD: df = 1; C PD vs. LBD: df = 1; D ED vs. Psychosis, df =1; E PD vs. Psychosis, df =1;…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Hence, such approaches can inform not only if the treatment works, but can help identify the possible mechanism by which it works; the neglect of which is a criticism of the research on CBT for psychosis (Thomas, 2015). Wilson et al (2016) reported that the treatment was acceptable, and individuals who had good outcomes showed the expected change on appraisals of threat. However, the work was limited in terms of the therapy and methodology.…”
Section: Cognitive Behavioural Therapy For Vhmentioning
confidence: 99%
“…A semi-structured interview was used to capture the participants' experiences of therapy, including acceptability, and any beneficial or adverse effects of treatment. It was based on The Change Interview (Elliot et al, 2001) and the work of Wilson et al (2016). The interview was completed once at the end of the intervention phase.…”
Section: Post-treatment Interviewmentioning
confidence: 99%